The The Effect Of Company Size And Debt Policy On Companies In The Technology Sector - Bangun, Yulia Ribuna Br Bangun; Annisa Khairani; Abel Sonia S; An Suci Azzahra (International Journal of Economic Research and Financial Accounting, 2025)
This study aims to determine the effect of company size and debt policy on firm value in technology sector companies that are included in the IDX list for the 2020-2023 period. The research sample consisted of 16 companies selected by applying purposive sampling method. Multiple regression analysis is applied to be the data analysis method in this study. The type of data used is secondary data obtained from www.idx.co.id. The results of this study show that company size and debt policy have a partial but significant effect on firm value.